Low‐dose tyrosine kinase inhibitors before treatment discontinuation do not impair treatment‐free remission in chronic myeloid leukemia patients: Results of a retrospective study. Issue 15 (27th May 2020) - Cayssials, Emilie; Torregrosa‐Diaz, Jose; Gallego‐Hernanz, Pilar; Tartarin, Florence; Systchenko, Thomas; Maillard, Natacha; Desmier, Déborah; Machet, Antoine; Fleck, Emmanuel; Corby, Anne; Motard, Carine; Denis, Guillaume; et al.
Abstract : Background: Long‐term treatment‐free remission (TFR) represents a new goal for chronic myeloid leukemia (CML). In clinical practice, tyrosine kinase inhibitor (TKI) dose reductions can be considered a means of preventing adverse effects and improving quality of life. We hypothesized that administration of low‐dose TKIs before treatment discontinuation does not impair TFR in patients with CML who have a deep molecular response (DMR, ≥MR 4 ). Methods: We conducted a retrospective analysis of 77 patients with CML who discontinued treatment with TKIs. Twenty‐six patients had been managed with low‐dose TKIs before stopping treatment. Patients were to be exposed to TKIs for ≥5 years and to low‐dose TKIs for ≥1 year and in DMR for ≥2 years. The loss of major molecular response (MMR) was considered a trigger for restarting therapy. Results: In the low‐dose group, 61.5% of patients received second‐generation TKIs, and dose reduction was ≥50% for 65.4% of patients. With a median follow‐up of 61.5 months, TFR at 12 months was 56.8% in the full‐dose TKI group and 80.8% in the low‐dose group, and TFR at 60 months was 47.5% and 58.8%, respectively. The median time to molecular recurrence (≥MMR) from TKI discontinuation in the entire cohort was 6.2 months. All patients quickly achieved MMR after resuming TKI therapy. Results appear independent of both dose reduction and potential pretreatment with interferon‐α. Conclusion: This retrospective study shows that TFR was not impaired by low‐dose TKI regimens before TKI cessation in Patients with CML. Nevertheless, prospective randomized clinical trials must be undertaken to analyze the probability of successful TFR in patients managed with TKI dose de‐escalation strategies before TKI discontinuation. Abstract : We conducted a retrospective analysis of chronic myeloid leukemia patients who had been managed with low‐dose tyrosine kinase inhibitors (TKIs) and discontinued treatment to test the hypothesis that treatment‐free remission was not impaired by low‐dose TKI regimens (≥1 year) before treatment cessation.